Domestic rainwater harvesting interventions in Sri Lanka: some lessons learnt - Aheeyar, Mohamed M. M.; Ariyananda, T. (2014)
The lack of accessibility to safe drinking water is one of the primary constraints affecting rural livelihoods, especially in the Dry Zone of Sri Lanka. This situation affects the poor more than the rich people in the community. Rainwater harvesting systems (RWHS) were implemented using the roof as the catchment at household level under subsidized schemes, which was a measure to minimize water and sanitation issues. The harvested rainwater was intended to be used for drinking and other domestic purposes with or without treatment. Assessment of the current status of RWHS in the country shows that there is a high correlation between the lack of some of the essential components of RWHS and non-use of the system. All the systems that were not being used lacked one or more of the essential components of a typical RWHS, such as gutters, tank lid, filter and first flush device. Due to the subsidized scheme, part of the system was provided by the beneficiaries in order to get ownership. Economic reasons and the willingness to use rainwater delayed providing the expected contribution to the beneficiary. With time, the system never became fully functional. There were some who made use of the system and maintained it fully, but this was around 50% of the original number of beneficiaries. Awareness also plays an important role in adoption of the system. As expected, almost all the beneficiaries who had undertaken routine maintenance of RWHS used the harvested rainwater for drinking purposes. Abandonment of systems takes place when the system provided is incomplete or if it lacks one or more of the essential components.